Systematic Literature Review: Kecurangan Laporan Keuangan Di Indonesia Dan Malaysia - Juli Rima Afiani; Dwi Cahyono; Gardina Aulin Nuha (LPPM POLITEKNIK LP3I BANDUNG, 2022)
This study aims to identify and analyze literature related to financial statement fraud in Indonesia and Malaysia. The method used in this study is the Systematic Literature Review (SLR) of journal papers for the 2016-2021 period. The literature review process consists of three stages, namely planning, implementation and reporting using the PRISMA (Preferred Reporting Items for Systematic Review and Meta Analyses) research design which includes several processes. The initial study found 121 research articles using the Scopus database with the Publish or Perish application, and the total study used was 10 articles based on inclusion and exclusion criteria. There are four research questions raised in this study. The results of research published in journals published in 2016-2021 state that the factors for fraudulent financial statements in Indonesia are weak auditors, ineffective audit committee supervision, weak internal controls, weak governance and client engagement with borrowers. While the factors of financial statement fraud in Malaysia are audit committee involvement, weak governance and low earnings management. The researcher concludes that financial statement fraud that occurs in Indonesia and Malaysia can occur due to pressure and opportunities that occur due to weak internal and external controls. Keywords: Systematic Literature Review (SLR), fraudulent financial statements, Indonesia, Malaysia